Persepsi Petani terhadap Penetapan Subak sebagai Warisan Budaya Dunia (Studi Kasus Subak Pulagan Kawasan Kecamatan Tampaksiring Kabupaten Gianyar) - SARITA, AYU FEBY; WINDIA, I WAYAN; SUDARTA, I WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2013)
ABSTRACT Farmers’ Perception toward Awarding Degree Subak as World Cultural Heritage - Study Case in Subak Pulagan Tampaksiring District Gianyar Region Subak is the organization that regulates the irrigation system used in the rice field in Bali. Subak unique culture has an element of mutual support and the concept of Tri Hita Karana makes UNESCO decided to give awarding degree to subak as world cultural heritage. One of that subak is Subak Pulagan which one fed by the watershed (DAS) Pakerisan. Respondents in this research were 34 farmers taken from 160 farmers decided by random sampling method. Perceptions and expectations seen from three aspects, they’re mindset, social, and material aspects. Data analysis is done by descriptive – qualitative calculations using Likert scale. Perceptions result shown 83.63% or on good category. Almost all respondents said the response was excellent or agree with the statement in the questionnaires. Farmers' perceptions based on aspects of mindset has score 73.53% or on good category, social aspect’s score is 90.76% or on very well category, and material aspects’s score is 86.62% which is on very good category. They have hopes to make farmer’s life better in the future. Based on this study it can be seen that the members of Subak Pulagan still need the things related to improving productivity and enhancing the quality of life in order to retain continuity subak. Keywords : perceptions, subak, world heritage.